Virginia Woolf and Christian culture - De Gay, Jane, 1966- (Edinburgh University Press, 2017)
This wide-ranging study demonstrates that Woolf, despite her agnostic upbringing, was profoundly interested in, and knowledgeable about, Christianity as a faith and a socio-political movement.
Keywords: Woolf, Virginia, -- 1882-1941.; Woolf, Virginia, -- 1882-1941; Culture -- Religious aspects.; Christianity -- 20th century.; Christianisme -- 20e siècle.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; PERFORMING ARTS -- Acting & Auditioning.; Christianity; Culture -- Religious aspects; 1900-1999